Gender heterogeneity and politics in decision-making about green public procurement in the Czech Republic - Michal Plaček; Cristina del Campo; Vladislav Valentinov; Gabriela Vaceková; Markéta Šumpíková; František Ochrana (Politics and Governance, 2022)
Green public procurement (GPP) is a widely recognized public policy tool that has attracted considerable scholarly research. However, much of this research has paid little attention to the nature of discretionary decision-making on the part of bureaucrats and local politicians; nor has it recognized that a crucial determinant of the implementation of GPP is the extent to which women hold administrative and political positions. While GPP tends to be discussed as a tool for promoting gender equality, we draw on feminist insights to argue that doing so may be a tool for enhancing the uptake and implementation of GPP. Utilizing the data from a large-N survey among local politicians and upper-echelon bureaucrats in the Czech Republic, we develop a path analysis model exploring the influence of gender on their decision-making. The results give credence to our overall argument that women are more likely to promote GPP. This argument not only breaks new ground by revealing the gendered nature of GPP but also generates straightforward policy implications.
Keywords: 320; decision-making; gender; green public procurement